Comparative analysis of counter-current and co-current downer reactors using particle image velocimetry and computational particle-fluid dynamics - Talal A. Aldugman; Mengmeng Cui; Abdulrahman Alzailaie; Abdullah Alhareth; Kenneth Langley; Lujain Alfilfil; Khalid Almajnouni; Jorge Gascon; Sigurdur Thoroddsen; Pedro Castaño (Chemical Engineering Journal Advances)
We investigated the hydrodynamics in co- and counter-current downer operations using particle image velocimetry (PIV) and computational particle fluid dynamics simulations (CPFD). Pilot-scale experiments were conducted for fluid catalytic cracking (FCC) catalysts and sand, which verified the system stability and provided the validation basis for the simulation strategy. We compared the reactor characteristics of counter-current and co-current downers under different operating modes and conditions using PIV experiments and CPFD simulations. PIV experiments showed that the counter-current downer exhibits a more uniform particle velocity profile, with a gradient of only 8 % of the maximum velocity, compared to the co-current operation, which shows a significantly steeper gradient of 39.5 % from the maximum. Simulations confirmed that the counter-current downer reactor has 69 % higher solid holdup and 98 % longer residence time than the co-current operation. Thus, the counter-current downer reactor demonstrated intermediate behavior between the classical co-current downer and riser reactors, offering flexibility for industrial applications.